2002
DOI: 10.1136/ard.61.7.646
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing patients with longstanding shoulder joint pain

Abstract: Objective: To examine the interobserver agreement of commonly used clinical tests and diagnoses in patients with shoulder pain, and the accuracy of these tests and ultrasonographic findings in comparison with arthroscopic findings. Methods: Eighty six patients with longstanding shoulder joint pain were "blindly" examined by two trained doctors using several clinical tests. In all patients an ultrasonographic examination was performed, and in 42 (49%) an arthroscopy. Results: Tests for impingement showed poor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 13 publications
1
27
0
1
Order By: Relevance
“…They concluded that ultrasound is a highly accurate diagnostic method for detecting full-thickness rotator cuff tears, but is less sensitive in detecting partial-thickness rotator cuff tears. This is in agreement with the results of Norregaard et al (2002) who found ultrasound to be less sensitive for detecting partialthickness rotator cuff tears and ruptures of the biceps tendons. Nonetheless ultrasound is quick, non-invasive, and relatively inexpensive; hence it should be used wherever possible to improve diagnosis and treatment of painful shoulder even though the effectiveness of ultrasound is dependent on the type of disorder and the skills and experience levels of the operator (O 'Connor et al, 2005).…”
Section: Ultrasoundsupporting
confidence: 92%
“…They concluded that ultrasound is a highly accurate diagnostic method for detecting full-thickness rotator cuff tears, but is less sensitive in detecting partial-thickness rotator cuff tears. This is in agreement with the results of Norregaard et al (2002) who found ultrasound to be less sensitive for detecting partialthickness rotator cuff tears and ruptures of the biceps tendons. Nonetheless ultrasound is quick, non-invasive, and relatively inexpensive; hence it should be used wherever possible to improve diagnosis and treatment of painful shoulder even though the effectiveness of ultrasound is dependent on the type of disorder and the skills and experience levels of the operator (O 'Connor et al, 2005).…”
Section: Ultrasoundsupporting
confidence: 92%
“…Although many of the clinical diagnostic criteria for these specific shoulder disorders have been widely published and taught, perhaps because of the complex anatomical and functional structure, there is evidence to suggest that these patho-anatomical classification systems do not generally perform reliably in practice [23][24][25][26][27]. Their validity, at least in population and workplace studies, has also been questioned.…”
Section: Acromioclavicular Joint Syndromementioning
confidence: 99%
“…Only acceptable interexaminer reliability was reported by NØrregaard et al (2002) in patients with longstanding shoulder pain. For Neer impingement sign, good interexaminer reliability was reported when patients with hemiplegic shoulder pain were evaluated (Dromerick et al, 2006).…”
Section: Introductionmentioning
confidence: 97%